# Maths Wiz Solutions Class 8 Chapter 6

## Maths Wiz Class 8 Solutions Chapter 6 Factorisation of Algebraic Expressions

Welcome to NCTB Solutions. Here with this post we are going to help 8th class students for the Solutions of Maths Wiz Class 8 Math Book, Chapter 6, Factorisation of Algebraic Expressions. Here students can easily find step by step solutions of all the problems for Factorisation of Algebraic Expressions, Exercise 6A, 6B, 6C, 6D, 6E, 6F and 6G Also here our mathematics teacher’s are solved all the problems with easily understandable methods with proper guidance so that all the students can understand easily. Here in this post students will get chapter 6 solutions. Here in this post all the solutions are based on ICSE latest Syllabus.

Factorisation of Algebraic Expressions Exercise 6A Solution :

Question no – (1)

Solution :

(a) 4x + 8y = 4 (x + 2y)

(b) 9m – 3 = 3(3m – 1)

(c) 5b2 – 20b = 5b (b – 4)

(d) – 3ax + 6ay = -3a (x + 2y)

(e) 3x2y2 – xy2 = xy2 (3x – 1)

(f) 14a3b – 7a2b2 = 7a2b (2a – b)

(g) – xy – 3x = – x (y + 3)

(h) 8×3 – 28x2 – 4x = 4x (2x– 7x – 2)

Question no – (2)

Solution :

(a) 7x + 28 = 7 (x + 4)

(b) 15y – 3 = 3 (5y – 1)

(c) 600x – x2 = x (600 – x)

(d) – 3x – 27 = -3 (x + 9)

(e) 50x5 – 25x4 + 100x3 = 25x3 2x2 – x + 4

(f) – 3y2 – 9y3 = – 3y(1 + 3y)

Question no – (3)

Solution :

(a) ax2 + ay

= a(x2 + y)

(b) 4a2 – 2a2c

= 2a2 (2 – c)

(c) 28p3 – 42p2q

= 14p2 (2p – 3q)

(d) – 15p2 – 20pr

= – 5p (3p + 4r)

(e) –m2n – mn2

= – mn (m + n)

(f) 48y5z3 – 64y4z4

= 16y4z3 (3y – 4z)

(g) 21y3 – 14y2 – 7y

= 7y (3y2 – 2y – 1)

(h) 16x3y2 – 20x2y3 – 28x2y2z

= 4x2y2 (4x – 5y – 7z)

Factorisation of Algebraic Expressions Exercise 6B Solution :

Question no – (1)

Solution :

Given, a (f + g) + b(f + g)

a (f + g) + b(f + g)

= (f + g) (a + b)

Question no – (2)

Solution :

Given, x (b – c) – y(b – c)

x (b – c) – y(b – c)

= (b – c) (x – y)

Question no – (3)

Solution :

Given, p2 (x + y) + q(x + y)

p2 (x + y) + q(x + y)

= (x + y) (p2 + q2)

Question no – (4)

Solution :

Given, 3(6 – y) – y(6 – y)

3(6 – y) – y(6 – y)

= (6 – y) (3 – y)

Question no – (5)

Solution :

Given, a (10 – x) – (10 – x)

a (10 – x) – (10 – x)

= (10 – x) (a – 1)

Question no – (6)

Solution :

Given, (a – b)2 + 4(a – b)

(a – b)2 + 4(a – b)

= (a – b) (a – b + 4)

Question no – (7)

Solution :

Given, 4(p + q)2 – 8(p + q)

4(p + q)2 – 8(p + q)

= (p + q) (4p + 4q – 8)

Question no – (8)

Solution :

Given, 7x + 14y + (x + 2y)2

7x + 14y + (x + 2y)2

= 7(x + 2y) + (x + 2y) (x + 2y)

= (x + 2y) (x + 2y + 7)

Question no – (9)

Solution :

Given, (5y – 3z)2 – 10y + 6z

(5y – 3z)2 – 10y + 6z

= (5y – 3z) (5y – 3z) – 2 (5y – 3z)

= (5y – 3z) (5y – 3z – 2)

Question no – (10)

Solution :

Given, 3x(x – y) + 2y(x – y) + 7(y – x)

3x(x – y) + 2y(x – y) + 7(y – x)

= 3 (x – y) + 2y(x – y) – 7(x – y)

= (x – y) (3x + 2y – 7)

Question no – (11)

Solution :

Given, 10 + 2y – 5z – zy

10 + 2y – 5z – zy

= 2(5 + y) – 5z (5 + y)

= (2 – 5z) (5 + y)

Question no – (12)

Solution :

Given, 2pq – 6p + q – 3

2pq – 6p + q – 3

= 2p (q – 3) + 1 (q – 3)

= (q – 3) (2p + 1)

Factorisation of Algebraic Expressions Exercise 6C Solution :

Question no – (1)

Solution :

Given, ax2 + by2 + bx2 + ay2

ax2 + bx2 + ay2 + by2

= x2 (a + b) + y2 (a + b)

= (a + b) (x2 + y2)

Question no – (2)

Solution :

Given, my + nz + mz + ny

my + mz + ny + nz

= m (y + z) + n (y + z)

= (m + n) (y + z)

Question no – (3)

Solution :

Given, ab – 5c + 5a – bc

ab + 5a – bc – 5c

= a (b + 5) – c (b + 5)

= (b + 5) (a – c)

Question no – (4)

Solution :

Given, x2 + ab – ax – bx

x2 – ax – bx + ab

= x (x – a) – b (x – a)

= (x – a) (x – b)

Question no – (5)

Solution :

Given, ab2 – bc2 – ab + c2

ab– ab – bc2 + c2

= ab (b – 1) – c2 (b – 1)

= (ab – c2) (b – 1)

Question no – (6)

Solution :

Given, 2xw – 3 – 6x + w

2xw + w – 6x – 3

= w (2x + 1) – 3 (2x + 1)

= (2x + 1) (w – 3)

Question no – (7)

Solution :

Given, 54x + 10y – 12xy – 45

54x – 12xy – 45 + 10y

= 6x (9 – 2y) – 5 (9 – 2y)

= (6x – 5) (9 – 2y)

Question no – (8)

Solution :

Given, m3 + 4m + 5m2 + 20

= m3 + 5m2 + 4m + 20

= m2 (m + 5) + 4 (m + 5)

= (m2 + 4) (m + 5)

Question no – (9)

Solution :

Given, 2axy2 + 10x + 3ay2 + 15

= 2axy2 + 3ay2 + 10x + 15

= ay2 (2x + 3) + 5 (2x + 3)

= (ay2 + 5) (2x + 3)

Factorisation of Algebraic Expressions Exercise 6D Solution :

Question no – (1)

Solution :

Given, a2 + 4ab + 4b2

a2 + 4ab + 4b2

= (a)2 + 2.a.2b + (2b)2

= (a + 2b)2

Question no – (2)

Solution :

Given, 4x2 – 4x + 1

4x2 – 4x + 1

= (2x)2 – 2.2x.1 + (1)2

= (2x – 1)2

Question no – (3)

Solution :

Given, 36p2 – 60pq + 25q2

36p2 – 60pq + 25q2

= (6p)2 – 2.6p.5q + (5q)2

= (6p – 5q)2

Question no – (4)

Solution :

Given, x2 – 2xy – y2

= x2 – 2xy – y2

= (x)2 – 2.x.y – (y)2

No, it is not a trinomial square.

Question no – (5)

Solution :

Given, 49y2 – 14y + 1

49y2 – 14y + 1

= (7y)2 – 2.7y .1 + (1)2

= (7y – 1)2

Question no – (6)

Solution :

Given, 9x2y2 + 6xyz + z2

9x2y2 + 6xyz + z2

= (3xy)2 + 2.3xy.z + (z)2

= (3xy + z)2

Question no – (7)

Solution :

Given, 4m2 + 24m + 9

= 4m2 + 24m + 9

= (2m)2 + 2.2m.3.2 + (3)2

No, it is not a trinomial square.

Question no – (8)

Solution :

Given, 16b2 – 60by + 25y2

= 16b2 – 60by + 25y2

= (4b)2 – 2.4b.5y.3 + (5y)2

No, it is not a trinomial square.

Question no – (9)

Solution :

Given, 49x4 – 112x2y2 + 64y4

49x4 – 112x2y2 + 64y4

= (7x2)2 – 2.7x2.8y2 + (8y2)2

= (7x2 – 8y2)2

Question no – (10)

Solution :

Given, 25x2 + 20x + 1

= (5x)2 + 2.5x.2 + 1

No, it is not a trinomial square.

Question no – (11)

Solution :

Given, x2/9y2 – 1/15 + y2/25x2

x2/9y2 – 1/15 + y2/25x2

= (x/3y)2 + 2.x/3y.y/5x + (y/5x)2

= (x/3y + y/5x)2

Question no – (12)

Solution :

Given, a2 + a + 1/4

a2 + a + 1/4

= (a)2 + 2.a.1/2 + (1/2)2

= (a + 1/2)2

Question no – (13)

Solution :

Given, 1 + 18pq + 81p2q2

1 + 18pq + 81p2q2

= 1 + 2.9pq + (9pq)2

= (1 + 9pq)2

Question no – (14)

Solution :

Given, 4 – 20b + 25b2

4 – 20b + 25b2

= (2)2 – 2.2.5b + (5b)2

= (2 – 5b)2

Question no – (15)

Solution :

Given, 4/9 x2 + 16/15 xy + 16/25 y2

4/9 x2 + 16/15 xy + 16/25 y2

= (2/3x)2 + 2.2/3x. 4/5y + (4/5y)2

= (2/3x + 4/5y)2

Factorisation of Algebraic Expressions Exercise 6E Solution :

Question no – (1)

Solution :

(a) Given, y2 – 9

∴ y2 – 9

= (y)2 – (3)2

= (y – 3) (y + 3)

(b) x2 – 25

∴ x2 – 25

= (x)2 – (5)2

= (x – 5) (x + 5)

(c) 9x2 – 4

∴ 9x2 – 4

= (3x)2 – (2)2

= (3x – 2) (3x + 2)

(d) 49x2 – 64

49x2 – 64

= (7x)2 – (8)2

= (7x – 8) (7x + 8)

(e) -16 + x2

-16 + x2

= (x)2 – (4)2

= (x – 4) (x + 4)

(f) p6 – 36

p6 – 36

= (p3)2 – (6)2

= (p3 – 6) (p3 + 6)

(g) 144x4y2 – z2

144x4y2 – z2

= (12x2y)2 – (z)2

= (12x2y – z) (12x2y + z)

(h) x6 – y4

x6 – y4

= (x3)2 – (y2)2

= (x3 – y2) (x3 +y2)

(i) a2/9 – b2/16

a2/9 – b2/16

= (a/3)2 – (b/4)2

= (a/3 – b/4) (a/3 + b/4)

(j) Given, 121/9m2 – n2

121/9m2 – n2

= (11/3m)2 – (n)2

= (11/3m + n) (11/3 m – n)

(k) Given, 25/36 x8 – y4

25/36 x8 – y4

= (5/6 x4)2 – (y2)2

= (5/6 x4 – y2) (5/6 x4 + y2)

(l) Given, – 25 + 1/64b2

– 25 + 1/64b2

= (1/8b)2 – (5)2

= (b/8 – 5) (b/8 + 5)

Question no – (2)

Solution :

(a) x2 + 8x + 16 – y2

x2 + 8x + 16 – y2

= x2 + 2.x.4 + (4)2 – y2

= (x + 4)2 – y2

= (x + 4 + y) (x + 4 – y)

(b) (a – b)2 – x2

∴ (a – b)2 – x2

= (a – b + x) (a – b – x)

(c) b2 – 6b + 9 – c2

b2 – 6b + 9 – c2

= (b)2 – 2.b.3 + (3)2 – c2

= (b – 3)2 – c2

= (b – 3 – c) (b – 3 + c)

(d) y2 – b– 8b – 16

y2 – b– 8b – 16

= y2 – {b2 + 2.4.b + (4)2}

= y2 – (b + 4)2

= (y – b – 4) (y + b + 4)

(e) x2 – c2 – 4 + 4c

∴ x2 – c2 – 4 + 4c

= x2 – (c2 – 4c + 4)

= x2 – (c2 – 2.c.2 + (2)2)

= x2 – (c – 2)2

= (x – c + 2) (x + c – 2)

(f) a2 – b2 – 10bc – 25c2

∴ a2 – b2 – 10bc – 25c2

= a2 – {b2 + 2.b.5c + (5c)2}

= a– (b + 5c)2

= (a – b – 5c) (a + b + 5c)

Question no – (3)

Solution :

(a) 5p2 – 5

∴ 5p2 – 5

= 5 (p2 – 1)

= 5 (p – 1) (p + 1)

(b) 8a2 – 32

8a2 – 32

= 8{a2 – 4}

= 8 (a2 – b2)

= 8 (a – 2) (a + 2)

(c) 16 – 100x2y2

16 – 100x2y2

= (4)2 – (10xy)2

= (4 – 10xy) (4 + 10xy)

(d) 2a3b4 – 98ab2

2a3b4 – 98ab2

= 2ab2 (a2b2 – 49)

= 2ab2 {(ab)2 – (7)2}

= 2ab2 (ab – 7) (ab + 7)

(e) c2 – 6c + 9 – y2

c2 – 6c + 9 – y2

= c2 – 2.c.3 + (3)2 – y2

= (c – 3)2 – y2

= (c – 3 – y) (c – 3 + y)

(f) x3 + x2 – 4x – 4

x3 + x2 – 4x – 4

= x2 (x + 1) – 4 (x + 1)

= (x2 – 4) (x + 1)

= (x – 2) (x + 2) (x + 1)

(g) m3 – mn2 – m2 + n2

m3 – mn2 – m2 + n2

= m (m2 – n2) – (m2 – n2)

= (m – 1) (m2 – n2)

= (m – 1) (m – n) (m + n)

Factorisation of Algebraic Expressions Exercise 6F Solution :

Question no – (1)

Solution :

Given, y2 + 4y + 3

y2 + 4y + 3

= y2 + 3y + y + 3

= y ( y + 3) + 1(y + 3)

= (y + 1) (y + 3)

Question no – (2)

Solution :

Given, a2 + 12a + 27

a2 + 12a + 27

= a2 + 9a + 3a + 27

= a (a + 9) + 3 (a + 9)

= (a + 3) (a + 9)

Question no – (3)

Solution :

Given, x2 + 12x + 32

x2 + 12x + 32

= x2 + 8x + 4x + 32

= x (x + 8) + 4 (x + 8)

= (x + 4) (x + 8)

Question no – (4)

Solution :

Given, p2 – 11p + 24

p2 – 11p + 24

= p2 – 8p – 3p + 24

= p (p – 8) – 3 (p – 8)

= (p – 8) (p – 3)

Question no – (5)

Solution :

Given, x2 – 15x + 44

∴ x2 – 15x + 44

= x2 – 11x – 4x + 44

= x (x – 11) – 4 (x – 11)

= (x – 4) (x – 11)

Question no – (6)

Solution :

Given, m2 – 15m + 56

∴ m2 – 15m + 56

= m2 – 7m – 8m + 56

= m (m – 7) – 8 (m – 7)

= (m – 8) (m – 7)

Question no – (7)

Solution :

Given, x2 + x – 30

x2 + x – 30

= x2 + 6x – 5x – 30

= x (x + 6) – 5(x + 6)

= (x – 5) (x + 6)

Question no – (8)

Solution :

Given, a2 – 3a – 18

a2 – 3a – 18

= a2 – 6a + 3a – 18

= a (a – 6) + 3 (a – 6)

= (a + 3) (a – 6)

Question no – (9)

Solution :

Given, b2 – b – 56

b2 – b – 56

= b2 – 8b + 7b – 56

= b (b – 8) + 7 (b – 8)

= (b – 8) (b + 7)

Question no – (10)

Solution :

Given, t2 – 20t  – 125

t2 – 20t  – 125

= t2 – 25t + 5t – 125

= t (t – 25) + 5 (t – 25)

= (t – 25) (t + 5)

Question no – (11)

Solution :

Given, u2 – 7u – 30

u2 – 7u – 30

= u2 – 10u + 3u – 30

= u (u – 10) + 3 (u – 10)

= (u + 3) (u – 10)

Question no – (12)

Solution :

Given, x2 – 43x + 42

x2 – 43x + 42

= x2 – 42x – x + 42

= x (x – 42) – 1(x – 42)

= (x – 1) (x – 42)

Question no – (13)

Solution :

Given, k2 + 12k – 160

k2 + 12k – 160

= k2 + 20k – 8k – 160

= k (k + 20) – 8 (k + 20)

= (k + 20) (k – 8)

Question no – (14)

Solution :

Given, x2 + 5x – 24

x2 + 5x – 24

= x2 + 8x – 3x – 24

= x (x + 8) – 3 (x + 8)

= (x – 3) (x + 8)

Question no – (15)

Solution :

Given, c2 – 19c + 78

c2 – 19c + 78

= c2 – 13c – 6c + 78

= c (c – 13) – 6 (c – 13)

= (c – 13) (c – 6)

Question no – (16)

Solution :

Given, y2 + 2y – 48

y2 + 2y – 48

= y2 + 8y – 6y – 48

= y (y + 8) – 6 (y + 8)

= (y – 6) (y + 8)

Question no – (17)

Solution :

Given, a2 + 9a – 36

a2 + 9a – 36

= a2 + 12a – 3a – 36

= a (a + 12) – 3 (a + 12)

= (a + 12) (a – 3)

Question no – (18)

Solution :

Given, m2 – 3m – 40

m2 – 3m – 40

= m2 – 8m + 5m – 40

= m (m – 8) + 5 (m – 8)

= (m + 5) ( m – 8)

Question no – (19)

Solution :

Given, t2 – 17t – 84

t2 – 17t – 84

= t2 – 21t + 4t – 84

= t (t – 21) + 4 (t – 21)

= (t + 4) (t – 21)

Question no – (20)

Solution :

Given, x2 – 13x – 68

x2 – 13x – 68

= x2 – 17x + 4x – 68

= x (x – 17) + 4 (x – 17)

= (x + 4) (x – 17)

Question no – (21)

Solution :

Given, u2 + 6u – 112

u2 + 6u – 112

= u2 + 14u – 8u – 112

= u (u + 14) – 8 (u + 14)

= (u – 8) (u + 14)

Factorisation of Algebraic Expressions Exercise 6G Solution :

Question no – (1)

Solution :

Given, 2x2 + 11x + 15

2x2 + 11x + 15

= 2x2 + 6x + 5x + 15

= 2x (x + 3) + 5 (x + 3)

= (2x + 5) (x + 3)

Question no -(2)

Solution :

Given, 6x2 + 17x + 5

6x2 + 17x + 5

= 6x2 + 15x + 2x + 5

= 3x (2x + 5) + 1 (2x + 5)

= (3x + 1) (2x + 5)

Question no – (3)

Solution :

3x2 + 11x + 5

3x2 + 11x + 5

= 3x2 + 6x + 5x + 10

= 3x (x + 2) + 5 (x + 2)

= (3x + 5) (x + 2)

Question no – (4)

Solution :

5b2 + 16b + 3

5b2 + 16b + 3

= 5b2 + 15b + b + 3

= 5b (b + 3) + 1 (b + 3)

= (5b + 1) (b + 3)

Question no – (5)

Solution :

3x2 + 13x + 12

3x2 + 13x + 12

= 3x2 + 9x + 4x + 12

= 3x (x + 3) + 4 (x + 3)

= (3x + 4) (x + 3)

Question no – (6)

Solution :

2x2 + 17x + 21

2x2 + 17x + 21

= 2x2 + 14x + 3x + 21

= 2x (x + 7) + 3 (x + 7)

= (2x + 3) (x + 7)

Question no – (7)

Solution :

15y2 + 16y + 4

15y2 + 16y + 4

= 15y2 + 10y + 6y + 4

= 5y (3y + 2) + 2 (3y + 2)

= (5y + 2) (3y + 2)

Question no – (8)

Solution :

6x2 + 17x – 14

6x2 + 17x – 14

= 6x2 + 21x – 4x – 14

= 3x (2x – 7) – 2 (2x – 7)

= (3x – 2) (2x – 7)

Question no – (9)

Solution :

4m2 + 7m – 2

4m2 + 7m – 2

= 4m2 + 8m – m – 2

= 4m (m + 2) – 1 (m + 2)

= (4m – 1) (m + 2)

Question no – (10)

Solution :

2x2 – 7x – 15

2x2 – 7x – 15

= 2x2 – 10x + 3x – 15

= 2x (x – 5) + 3 (x – 5)

= (2x + 3) (x – 5)

Question no – (11)

Solution :

5x2 – 16x + 3

5x2 – 16x + 3

= 5x2 – 15x – x + 3

= 5x (x – 3) – (x – 3)

= (5x – 1) (x – 3)

Question no – (12)

Solution :

6x2 – 17x + 12

6x2 – 17x + 12

= 6x2 – 9x – 8x + 12

= 3x (2x – 3) – 4 (2x – 3)

= (3x – 4) (2x – 3)

Question no – (13)

Solution :

5x2 + 9x – 18

5x2 + 9x – 18

= 5x2 + 15x – 6x – 18

= 5x (x + 3) – 6 (x + 3)

= (x + 3) (5x – 6)

Question no – (14)

Solution :

3x2 – x – 4

∴ 3x2 – x – 4

= 3x2 – 4x + 3x – 4

= x (3x – 4) + 1 (3x – 4)

= (x + 1) (3x – 4)

Question no – (15)

Solution :

8a2 + 18a – 5

8a2 + 18a – 5

= 8a2 + 20a – 2a – 5

= 4a (2a + 5) + 1 (2a + 5)

= (4a + 1) (2a + 5)

Question no – (16)

Solution :

8x2 – 73x + 9

8x2 – 73x + 9

= 8x2 – 72x – x + 9

= 8x (x – 9) – 1 (x – 9)

= (8x – 1) (x – 9)

Question no – (17)

Solution :

-2x2 + 5x + 42

-2x2 + 5x + 42

= – 2x2 + 12x – 7x + 42

= – 2x (x – 6) – 7 (x – 6)

= (x – 6) (- 2x – 7)

Question no – (18)

Solution :

-12x2 – 35x – 18

– 12x2 – 35x – 18

= -12x2 – 27x – 8x – 18

= – {12x+ 27x + 8x + 18}

= – {3x (4x + 9) + 2 (4x + 9)}

= – (3x + 2) (4x + 9)

Question no – (19)

Solution :

Given, – 2x2 – 15x – 7

– 2x2 – 15x – 7

= – 2x2 – 14x – x – 7

= – 2x (x – 7) – 1 (x – 7)

= – (2x + 1) (x – 7)

Question no – (20)

Solution :

30t2 + 39t – 9

30t2 + 39t – 9

= 30t2 + 15t – 6t – 9

= 15t (2t + 3) – 3 (2t + 3)

= (15t – 3) (2t + 3)

Question no – (21)

Solution :

15x4 – 10x3 – 25x2

15x4 – 10x3 – 25x2

= 15x4 – 25x3 + 15x3 – 25x2

= 5x3 (3x – 5) + 5x2 (3x – 5)

= (5x3 + 5x2) (3x – 5)

= 5 (x3 + x2) (3x – 5)

Question no – (22)

Solution :

14x3 – 57x2y – 27xy2

14x3 – 57x2y – 27xy2

= 14x3 – 63x2y + 6x2y – 27xy2

= 7x2 (2x – 9y) + 3xy (2x – 9y)

= (2x – 9y) (7x2 + 3xy)

Question no – (23)

Solution :

– 3x3 + 16x2 – 16x

– 3x3 + 16x2 – 16x

= – 3x2 + 12x2 + 4x– 16x

= – 3x2 (x – 4) + 4x (x – 4)

= (4x – 3x2) (x – 4)

Question no – (24)

Solution :

– 4x4 – 4x3 + 15x2

– 4x4 – 4x3 + 15x2

= – 4x4 – 10x3 + 6x3 + 15x2

= – 2x3 (2x + 5) + 3x2 (2x + 5)

= (3x2 – 2x3) (2x + 5)

Question no – (25)

Solution :

56x3 + 15x2 – 56x

56x3 + 15x2 – 56x

= 56x3 + (64 – 49) x2 – 56x

= 56x3 + 64x2 – 49x2 – 56x

= 8x2(7x + 8) – 7x (7x + 8)

= (8x2 – 7x) (7x + 8)

Question no – (26)

Solution :

32x4 + 12x3y – 5x2y2

32x4 + 12x3y – 5x2y2

= 32x4 + 20x3y – 8x3y – 5x2y

= 4x3 (8x + 5y) – x2y (8x + 5y)

= (4x3 – x2y) (8x + 5y)

Question no – (27)

Solution :

30m2 – 78mn + 36n2

30m2 – 78mn + 36n2

= 30m2 – 60mn – 18mn + 36n2

= 30m (m – 2n) – 18n (m – 2n)

= (30m – 18n) (m – 2n)

Next Chapter Solution :

Updated: June 19, 2023 — 2:00 pm